2018
DOI: 10.1007/s00421-018-3873-4
|View full text |Cite
|
Sign up to set email alerts
|

Right ventriculo–arterial uncoupling and impaired contractile reserve in obese patients with unexplained exercise intolerance

Abstract: BackgroundRight ventricular (RV) dysfunction and heart failure with preserved ejection fraction may contribute to exercise intolerance in obesity. To further define RV exercise responses, we investigated RV–arterial coupling in obesity with and without development of exercise pulmonary venous hypertension (ePVH).MethodsRV–arterial coupling defined as RV end-systolic elastance/pulmonary artery elastance (Ees/Ea) was calculated from invasive cardiopulmonary exercise test data in 6 controls, 8 obese patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…The absence of a significant exercise-induced increase in E/e' is in keeping with previous echocardiographic studies in healthy subjects (12,13,15). However, invasively measured pulmonary artery wedge pressure to estimate LAP has been reported in patients with obesity complaining of exercise dyspnea (9). Insufficient accuracy of LAP estimation from E/e' or insufficient maximal Q levels may account for the lack of a more sustained increase in LAP at exercise.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The absence of a significant exercise-induced increase in E/e' is in keeping with previous echocardiographic studies in healthy subjects (12,13,15). However, invasively measured pulmonary artery wedge pressure to estimate LAP has been reported in patients with obesity complaining of exercise dyspnea (9). Insufficient accuracy of LAP estimation from E/e' or insufficient maximal Q levels may account for the lack of a more sustained increase in LAP at exercise.…”
Section: Discussionsupporting
confidence: 85%
“…Previous echocardiographic and magnetic resonance imaging studies have shown that obesity is associated with increased RV dimensions and hypertrophy, and depressed indices of systolic function (6)(7)(8). This was confirmed by an invasive study, which reported on a decreased RV/PA coupling assessed by gold standard Ees/Ea that was correlated to a decreased exercise capacity and decreased PA compliance (9). In the present study, RV-PA coupling was estimated by the TAPSE/sPAP ratio.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, the increased work and afterload of the RV in PH were not accompanied by an equivalent increase in RV contractile function, particularly during exercise. The observation that maximal RV contractility in PH during exercise was not higher than in control is consistent with a recent observation in obese patients with exercise-induced PH and reduced exercise tolerance (30). Together with data showing E a is a robust and independent predictor of mortality in patients with WHO group 2 PH, and correlates strongly with RV dysfunction (16,43), it appears that the reduced RV contractile reserve, which results in a decrease in RV PA coupling during exercise, is an important limiting factor in exercise tolerance in PH patients.…”
Section: Rv O 2 Delivery In Relation To Rv Function and Exercise Capacitysupporting
confidence: 92%
“…35 In four of the six studies evaluating patients exercising in the upright position, a peak PAWP > 20 mmHg or a PAWP/CO slope > 2 mmHg/L/min was considered as a pathological threshold to define HFpEF. 3,4,24,28 Notably, six studies focused on specific HFpEF subpopulations, such as those with obesity, recent myocardial infarction, non-obstructive coronary artery disease, or patients included in an interventional trial. 20,24,29,32,34,36 Only in four studies the left ventricular ejection fraction to define HFpEF was >40% or >45%, rather than the currently adopted cut-off of ≥50%.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%